2008
DOI: 10.1029/2007ja012594
|View full text |Cite
|
Sign up to set email alerts
|

Coupling between density structures, electromagnetic waves and ionospheric feedback in the auroral zone

Abstract: [1] This paper presents results from a numerical study of nonlinear interactions between ultra-low-frequency (ULF) electromagnetic waves and the magnetospheric-ionospheric plasma at high latitudes. The study is motivated by observations of density cavities in the ionosphere in regions of downward field-aligned current adjacent to auroral arcs. The role of active ionospheric feedback in the development of intense, small-scale electromagnetic waves with frequencies of 0.1-1 Hz is considered, together with the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
118
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(143 citation statements)
references
References 44 publications
(84 reference statements)
23
118
2
Order By: Relevance
“…Such nonlinear motions can be excited by the Kelvin-Helmholtz instability giving rise to auroral curls [Hallinan and Davis, 1970]. Furthermore, ionospheric feedback instability [Atkinson, 1970;Holzer and Sato, 1973;Sato, 1978;Lysak, 1991;Streltsov and Lotko, 2008] can generate small-scale Alfvén waves due to the interaction with the ionosphere. While these processes are likely to operate and contribute to the structure in the aurora, the phase mixing process has the advantage that it is linear, so that it will operate even if the perturbations are not large, and it is also not affected by a low ionospheric conductivity, which is favored for ionospheric feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Such nonlinear motions can be excited by the Kelvin-Helmholtz instability giving rise to auroral curls [Hallinan and Davis, 1970]. Furthermore, ionospheric feedback instability [Atkinson, 1970;Holzer and Sato, 1973;Sato, 1978;Lysak, 1991;Streltsov and Lotko, 2008] can generate small-scale Alfvén waves due to the interaction with the ionosphere. While these processes are likely to operate and contribute to the structure in the aurora, the phase mixing process has the advantage that it is linear, so that it will operate even if the perturbations are not large, and it is also not affected by a low ionospheric conductivity, which is favored for ionospheric feedback.…”
Section: Discussionmentioning
confidence: 99%
“…In a simulation where the ionosphere is driven by an Alfvén wave with a period of 1 s, an eigenmode of the resonator is excited and ion upflow is driven by the ponderomotive (time-averaged nonlinear Lorentz) force similar to Streltsov and Lotko [2008] as well as by the centrifugal acceleration similar to Cladis [1986]. Note that unlike Streltsov and Lotko [2008], the present model does not use height-integrated conductivity and resolves the full dynamics of the E-layer plasma.…”
Section: Resultsmentioning
confidence: 99%
“…[39] The ponderomotive effect in IAR was considered previously by Streltsov and Lotko [2008] and Sydorenko et al [2008]. Figure 5 of Streltsov and Lotko [2008] shows modification of ion density by the ponderomotive force.…”
Section: Nonlinear Lorentz Force (The Ponderomotive Effect)mentioning
confidence: 99%
See 1 more Smart Citation
“…To formulate the boundary conditions at the lower boundary of the cavity, at first only Pedersen conductivity was involved, and then the Hall conductivity (Lysak & Yoshikawa 2006). Streltsov & Lotko (2008) included coupling to the slow mode in the basic model; Lysak et al (2013) and Waters et al (2013) included the coupling to the fast mode. Pokhotelov et al (2000) found frequency dispersion of the IAR eigenmode due to the Hall conductivity.…”
Section: Introductionmentioning
confidence: 99%